Labor market facing higher education surplus, trends and solutions (the case study of Israel) - LEVKOVICH Lavan Limor (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Since the 1990s, the government has increased outputs from higher education institutions in Israel, by increasing public funding for these institutions. The policy of increasing output was based on an approach according to which more accessible higher academic education is the key to growth on individual and national levels and narrowing gaps between weak and stronger populations. Added to these national steps, was the introduction of the information revolution and accelerated technological advancements that changed the structure of focus of the employment market in Israel and around the world. These processes even underwent a more aggressive tendentious change after the wave of global quarantines caused by the Corona pandemic. Hence, a negative educational-employment trend started which made education redundant. This article will examine the phenomenon in Israel, looking at what is happening around the world and the author’s proposals for feasible solutions.